Evaluating symmetry of the swing leg during running with velocity-velocity profiles - Jorden, R. A.; Heise, G. D.; Mallory, K.; Packard, D. (Annual Meeting of the American Society of Biomechanics. (Presented on poster September 9-10, 2004 at the ASB meeting in Portland), 2004)
Researchers who study running traditionally examine sagittal plane motion, and often assume that the kinematics of gait are symmetrical. Those who do study nonsagittal motion of the leg and foot often examine the stance phase of running. Studies which focus on rearfoot motion usually attempt to identify connections between frontal plane mechanics with a person's predisposition to leg and foot injuries (e.g., Williams et al., 2001). Focusing on the stance phase of running makes sense because of the high forces encountered by the single support leg; however, an analysis of lower extremity motion outside the sagittal plane during swing phase is often not addressed. In conclusion, the analysis was successful in classifying swing leg symmetry and it was found that all runners regardless of symmetry displayed high cycle repeatability.